Academic and social integration and their relation to dropping out of teacher education: a comparison to other study programs - Franz, Sebastian; Paetsch, Jennifer (Frontiers in Education, 2023)
Academic and social integration have been identified as key predictors of the decision to drop out by higher education students. So far, there is limited knowledge about whether there are differences in the degree of integration between teacher education students and students in other academic programs, although these differences might affect the decision-making process of students and their likelihood of dropping out. Furthermore, it is still unclear if the reasons for students dropping out of teacher education programs differ from those in other academic programs. This study aims to address this research gap by examining integration and dropout rates of 8,237 students who were studying to become teachers, compared to students in similar fields of study in German higher education. The data for the study were collected from the National Educational Panel Study (NEPS). The results revealed significant differences between teacher education students and other students in peer and faculty social integration, but not in normative and structural academic integration. However, no moderation effect of the teacher education program on the association of integration and dropout was found. The findings contribute to the discussion on causes of dropout in teacher education by showing higher values in peer social integration and lower values in faculty social integration for teacher education students. These results complement previous research by providing new findings on the causes of students’ decision to drop out of initial teacher education. Practical implications on how to increase retention in teacher education programs are discussed.